A comparison of the effects of flosequinan, a new vasodilator, and propranolol on sub-maximal exercise in healthy volunteers. - Lewis, H M (1989)
1. The effects of steady state flosequinan, a new vasodilator, and propranolol, on glucose mobilisation, lipolysis and plasma potassium concentration during sub-maximal exercise testing were investigated in a double-blind, randomised, three-way crossover study in 12 healthy volunteers. 2. Plasma glucose, potassium and free fatty acid concentration during and after exercise on flosequinan were similar to those on placebo. Exercise heart rates were 7% (+9.2 beats min-1) higher on flosequinan compared with placebo (P less than 0.05). During exercise on propranolol plasma glucose concentrations were comparable with those on placebo but plasma potassium concentrations were higher (mean increase 0.26 mmol l-1, P less than 0.01) whereas free fatty acid concentrations were lower (mean decrease 0.10 mmol 1-1, P less than 0.01). As expected the heart rate on exercise was 25% less (-35 beats min-1) on propranolol (P less than 0.05). 3. These data suggest that, in contrast to propranolol, flosequinan does not adversely affect the mobilisation of the two major sources of energy during sub-maximal exercise.